Effect of Puerperal Exercises and Auricular Acupressure on Uterine Involution - Rahmadini, Fhadilah; Elly, Nur; Buston, Erni; Yovalwan, Tahratul; Rahmadani, Wahyudi (Poltekkes Kemenkes Palu, 2024)
The process of uterine involution in postpartum mothers does not always proceed smoothly, potentially leading to subinvolution of the uterus and postpartum hemorrhage. This study aims to determine the influence of puerperal exercises and auricular acupressure on uterine involution in postpartum mothers. The research utilized a quasi-experimental design with a post-test only control group. The study was conducted in Bengkulu City. The sample consisted of 40 postpartum mothers, divided into 20 respondents in the intervention group receiving a combination of puerperal exercises and auricular acupressure, and 20 respondents in the control group receiving only puerperal exercises. Sampling technique was done through purposive sampling. The instruments used were a measuring tape and a questionnaire. Data analysis employed independent T-test. The results indicate a decrease in the height of the uterine fundus in both intervention and control groups, but the decrease in uterine involution was more significant in the intervention group (p=0.000). The study concludes that there is an influence of the combination of puerperal exercises and auricular acupressure on reducing uterine involution in postpartum mothers.